Parametrization of all stable stablizing controllers - Saif, A.-W.A. (1998)
The Youla parametrization of all stabilizing controllers is addressed using a stable controller. First a stable central controller is obtained. Then a constructive procedure to find the Youla free parameter Q is given such that the overall controller is stable